PENGARUH FRAUD DIAMOND TERHADAP FRAUDULENT FINANCIAL REPORTING - Dwianto, Agus; Setiawati, Erma; Puspitasari, Diana; Arum S, Nurlita (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
The objective of this study is to determine the influence of pressure (financial targets, financial stability, and external pressure), opportunities (industry characteristics and ineffective monitoring), opportunities (auditor turnover and rationalization), and capabilities on Fraudulent Financial Reporting in Manufacturing Companies listed on the Indonesia Stock Exchange from 2017 to 2021. The research approach employed a quantitative method, namely utilizing panel data regression analysis, with the assistance of Eviews 9.0 software. Financial objectives have a positive and significant influence on misleading financial reporting. Financial stability, rationalization, and poor monitoring have a significant negative impact on inaccurate financial reporting, while external pressure, industry type, auditor turnover, and capability do not have a significant influence on inaccurate financial reporting. In subsequent research, it is expected to include a greater number of independent variables and a larger sample size in order to yield more robust research findings.